Therapeutic Effects of Mesenchymal Stromal Cell-Derived Small Extracellular Vesicles in Oxygen-Induced Multi-Organ Disease: A Developmental Perspective - Fernandez-Gonzalez, Angeles; Willis, Gareth R.; Yeung, Vincent; Reis, Monica; Liu, Xianlan; Mitsialis, S. Alex; Kourembanas, Stella (Frontiers in Cell and Developmental Biology, 2021)
Despite major advances in neonatal intensive care, infants born at extremely low birth weight still face an increased risk for chronic illness that may persist into adulthood. Pulmonary, retinal, and neurocognitive morbidities associated with preterm birth remain widespread despite interventions designed to minimize organ dysfunction. The design of therapeutic applications for preterm pathologies sharing common underlying triggers, such as fluctuations in oxygen supply or in the inflammatory state, requires alternative strategies that promote anti-inflammatory, pro-angiogenic, and trophic activities—ideally as a unitary treatment. Mesenchymal stem/stromal cell-derived extracellular vesicles (MEx) possess such inherent advantages, and they represent a most promising treatment candidate, as they have been shown to contribute to immunomodulation, homeostasis, and tissue regeneration. Current pre-clinical studies into the MEx mechanism of action are focusing on their restorative capability in the context of preterm birth-related pathologies, albeit not always with a multisystemic focus. This perspective will discuss the pathogenic mechanisms underlying the multisystemic lesions resulting from early-life disruption of normal physiology triggered by high oxygen exposures and pro-inflammatory conditions and introduce the application of MEx as immunomodulators and growth-promoting mediators for multisystem therapy.